2018
DOI: 10.1002/app.46707
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in mechanical properties of polyurethane‐urea nanocomposites by using modified SiO2 nanoparticles

Abstract: Poly(propylene glycol) (PPG)‐based nanocomposites have been prepared one shot using various contents of functionalized SiO2 nanoparticle as filler‐crosslinker agent. Triethoxy silyl propane‐1‐amine has been used as coupling agent for functionalization of SiO2 nanoparticle to improve its reactivity. The results revealed that the mechanical properties of the samples have been improved due to the functionalized SiO2‐nanoparticle effect on chemical and three‐dimensional physical crosslinking of the polyurethane–ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Foam density increased by 27% when the AgPL NPs content was 0.25% compared with the reference PUF-0 (Figure a). Incorporation of NPs chemically cross-linked with polyurethane has been described to improve the mechanical performance of the foams . In this study, the addition of AgPL NPs to the foams resulted in a 40% increase of their compression modulus, i.e., from 55 kPa for the reference PUF-0 to 78 and 77 kPa for PUF-0.20%NP and PUF-0.25%NP, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 72%
“…Foam density increased by 27% when the AgPL NPs content was 0.25% compared with the reference PUF-0 (Figure a). Incorporation of NPs chemically cross-linked with polyurethane has been described to improve the mechanical performance of the foams . In this study, the addition of AgPL NPs to the foams resulted in a 40% increase of their compression modulus, i.e., from 55 kPa for the reference PUF-0 to 78 and 77 kPa for PUF-0.20%NP and PUF-0.25%NP, respectively (Figure b).…”
Section: Resultsmentioning
confidence: 72%
“…38 Considerably, the fabricated elastomer via their suggested method could be reshaped and reprocessed by room-temperature compression through rearrangements of the cross-linked. 38 In continuous to our previous studies on self-healing materials [39][40][41][42][43] and polymer properties, 25,44 self-heal epoxy coatings have been prepared using disulfide metathesis reaction. In this regard, an epoxy terminated chain extender with capability of performing reversible reaction has been synthesized via functionalization of 3,3 0 -dithiodipropionic acid (DTPA) with bisphenol A diglycidyl ether (DGEBA).…”
Section: Introductionmentioning
confidence: 99%
“…In continuous to our previous studies on self‐healing materials 39–43 and polymer properties, 25,44 self‐heal epoxy coatings have been prepared using disulfide metathesis reaction. In this regard, an epoxy terminated chain extender with capability of performing reversible reaction has been synthesized via functionalization of 3,3′‐dithiodipropionic acid (DTPA) with bisphenol A diglycidyl ether (DGEBA).…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of NPs chemically cross-linked with polyurethane has been described to improve the mechanical performance of the foams. 235 In this study, the addition of AgPheLigNPs to the foams resulted in 40 % increase of their compression modulus, i. e. from 55 kPa for the reference PUF-0 to 78 kPa for PUF-0.20%NP and PUF-0.25%NP (Figure 38b). The results obtained from mechanical characterization of the PUFs suggested that the NPs are part of their structure and the lignin from the NPs may be covalently crosslinked with the polyols.…”
Section: Structural and Mechanical Characterization Of Pufsmentioning
confidence: 59%